Strategi Pengembangan Usaha Olahan Ikan Lomek di Dumai, Riau (Studi Kasus: Usaha Churros Ikan) - Shiffa Febyarandika Shalichaty; Kalvin Paiki; Ratu Sari Mardiah; Putri Wening Ratrinia (ACROPORA: Jurnal Ilmu Kelautan dan Perikanan Papua, 2021)
Lomek fish is a typical fish that is often found in the province of Riau, one of which is in Dumai. The stable production of lomek fishery in Dumai makes it necessary to have more management so that the catches obtained by fishermen are not only sold in the form of raw processing, but also in ready-to-sell products. The high potential of fish resources makes several products appear, one of which is churros made from lomek fish. This product diversification is also expected to improve the economy in Dumai City through MSMEs. The purpose of this study is to recommend a fish churros business development strategy using SWOT analysis. The results obtained are fish churros business based on SWOT analysis is in quadrant 1, namely the processing business must carry out aggressive efforts by taking advantage of strengths and opportunities, strategic recommendations that can be carried out are food certification, product registration in delivery services, collaboration and marketing in several markets. place, adding some variety to the taste of the product and providing price promotions to consumersKey Words: SWOT; Strategy; Business; Diversiification